Revitalization of Customary Law as an Instrument for Resolving Social Conflict in Multicultural Societies - Laros Tuhuteru (Journal of Adat Recht, 2025)
Customary law has long been an integral part of social conflict resolution in Indonesia, particularly in communities that still maintain local wisdom. This study aims to explore the role of customary law in social conflict resolution in multicultural societies and propose a model for revitalizing customary law that can be integrated with the state legal system. The method used is a qualitative approach with a case study design, involving in-depth interviews, document analysis, and field observations in several regions in Indonesia, including Sumatra, Kalimantan, Papua, and Bali. The results show that customary law remains relevant and effective in resolving social disputes through consensus-based mediation mechanisms. However, there are challenges in integrating traditional values ​​with modern legal norms, particularly those related to human rights and gender equality. This discussion proposes a hybrid model that combines customary law with state law, as well as formal recognition of customary mediation outcomes to increase its legitimacy and effectiveness. In conclusion, revitalizing customary law aligned with state legal principles can strengthen legal pluralism in Indonesia and improve inclusive social conflict resolution.